A high-speed integrated OFDM/DPS-OCDMA-based FSO transmission system: Impact of atmospheric conditions - Mehtab Singh; Somia A. Abd El-Mottaleb; Hassan Yousif Ahmed; Medien Zeghid; Kottakkaran Sooppy Nisar; Ameenah N. Al-Ahmadi; Mona Mahmoud (Alexandria Engineering Journal, 2023)
Free space optics (FSO) communication systems are preferred due to their high transmission capacity so it can support the ever-increasing volume of online traffic. Optical code division multiple access (OCDMA) is ideal for enhancing capacity by utilizing the same wavelengths for different information transmission. This paper presents a new FSO system based on the combination of orthogonal frequency division multiplexing (OFDM) and OCDMA systems. Three OCDMA channels, employing diagonal permutation shift (DPS) codes, carry 20 Gbps each, modulated by 4-level quadrature amplitude modulation (QAM) and OFDM. To assess performance, the proposed system considers severe climate conditions like rain, fog, and snow. The effectiveness is measured by bit error rate (BER) and received optical power (ROP). In addition, actual meteorological data for the cities of Alexandria, Egypt and Pune, India are evaluated to demonstrate the applicability of the proposed model in a real-world setting. The results reveal successful transmission with an overall capacity of 60 Gbps over a 3600 m FSO range in Alexandria, achieving a 0.27 dBm ROP. In Pune, with higher average rainfall, the maximum FSO link is 2750 m with a −0.06 ROP. Furthermore, the proposed model can propagate up to 850 m under weak turbulence (WT).